Glassy, amorphous and nano-crystalline materials : thermal physics, analysis, structure and properties - Sestak, Jaroslav 1938-; Mares, J., (Jiri), 1959-; Hubk̕, Pavel (New York : Springer, 2010)
Includes bibliographical references and index